PENINGKATAN KETERAMPILAN BERPIKIR KREATIF SISWA MELALUI IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DI SDN NAGRAK - Novianti, Nita; Sumantri, Muhammad Syarif; Gumelar, Gumgum (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2025)
Creativity is a 21st-century skill and also one of the dimensions of the Pancasila student profile that must be trained to students from an early age. To foster student creativity, efforts are needed to train creative thinking skills, one of which is in the Pancasila Student Profile Strengthening Project (P5) activities. The research is motivated by efforts made by schools to train students' creative thinking skills as one of the skills that students must master in responding to the challenges of the 21st century. This study aims to analyze the improvement of students' creative thinking skills in the implementation of the Pancasila Student Profile Strengthening Project (P5) which raises the theme of Sustainable Lifestyle at SDN Nagrak, Sukabumi City. This type of research uses classroom action research with 3 cycles. The technique of collecting written test data by calculating the average learning outcomes of each cycle, calculating the total score of the questionnaire and its descriptive analysis, and documentation. Likert scale questionnaires are given to the principal, teachers who teach in grade four, and nine students. The written test and questionnaire are carried out directly during the implementation of the P5 activities for three cycles. The results of the study showed a significant increase in students' creative thinking skills test results in the following indicators: 1) fluency; 2) flexibility; 3) originality; and 4) elaboration. These creative thinking skills can be practiced in P5 activities as an effective platform for building environmental awareness from an early age.